The Right to Political Party Membership in Ethiopia: On the Freedom to Join and Resign - Tesfay, Leake Mekonen (Mizan law review, 2018)
The FDRE Constitution acknowledges the right to freedom of political party membership. Similarly, the Political Parties Registration Proclamation, which regulates the details of political party membership, allows a political party member to withdraw from his/her membership at any time. The form of withdrawal, however, has become contentious. In Unity for Justice and Democracy Party -versus- Blue Party (a case finally adjudicated by the Cassation Bench of the Federal Supreme Court), the petitioner, claimed that a person cannot be member of another political party without a written withdrawal notice to his/her former political party. The respondent political party, on its part, argued that withdrawal from membership and taking membership in another political party is possible at any time. The points of controversy and the legal framework thereof are examined in this article. An attempt is made to assess relevant principles, international human rights instruments and the experience of other jurisdictions.